Suppose that $X_1, X_2, ..., X_n$ are independent, where each $X_i$ has probability (mass) function $p_i(x_i)$ given as $p_i(x_i) = \frac{e^{-\lambda} \lambda_i^{x_i}}{x_i!}$ (only the parameter $\lambda_i$ differs int he distribution of each $X_i$ for $x_i = 0, 1, ...$. What is the distribution of their sum: $\sum\limits_{i=1}^n X_i$ ? Prove it (perhaps with moment generating functions).

Answer: The moment generating function of Poisson (sum of $\lambda$)

I don't get how to do this question and I don't really understand the question. Can someone please help me? Thanks in advance.

  • 1
    $\begingroup$ May be start with 2, then n. What is the sum of two independent poisson random variables? $\endgroup$
    – vinux
    Apr 26, 2013 at 6:36
  • $\begingroup$ I still don't get it.. Isn't the sum of the two independent poisson random variables the product of its moment generating functions? $\endgroup$ Apr 26, 2013 at 6:42
  • $\begingroup$ No, the MGF of the distribution of the sum is the product of the MGFs. The MGF of the Poisson is simple. If you have trouble, you might like to let $a = (e^t - 1)$ and see how you go, then put $e^t-1$ back in for $a$ at the end. $\endgroup$
    – Glen_b
    Apr 26, 2013 at 6:50
  • $\begingroup$ @Sue, Through valid MGF (moment generating function) one can uniquely identify the random variable. follow Glen's correction. $\endgroup$
    – vinux
    Apr 26, 2013 at 6:57
  • 1
    $\begingroup$ The issue here is that the Answer given to Sue is not an answer to the question she has been asked: What is the distribution of their sum: $\sum_{i=1}^n X_i$? The correct answer to the question that she has been asked is that the sum has a Poisson distribution with parameter $\lambda=\sum_{i=1}^n \lambda_i$ and not The moment generating function of Poisson(sum of $\lambda$ ); that is the answer to a different question: What is the MGF of $\sum_{i=1}^n X_i$? $\endgroup$ Apr 26, 2013 at 11:19

1 Answer 1


The MGF is $\psi_{X_i}(t)=e^{\lambda_i(e^t-1)}$. The MGF of $S_n$, $S_n=\sum_{i=1}^n X_i$ is $\psi_{S_n}(t)=\prod_{i=1}^n \psi_{X_i}(t)$. So what we get is

$$ \prod_{i=1}^n \psi_{X_i}(t)=\prod_{i=1}^ne^{\lambda_i(e^t-1)}=e^{\sum_{i=1}^n\lambda_i(e^t-1)}=e^{\lambda^*(e^t-1)} $$ where $\lambda^*=\sum_{i=1}^n\lambda_i$. Since the result is the MGF of a Poisson with parameter $\lambda^*$, the conclusion is that the sum of independent Poisson random variables with different parameters is a Poisson random variable with the sum of their individual parameters as its parameter.

Edit: If it wasn't clear enough, the conclusion is this:

$$ \text{If }X_i \text{ are independently distributed, } X_i\sim Po(\lambda_i), \, i=1, \dots, n\\ \text{then } \sum_{i=1}^n X_i=S_n \sim Po\left(\sum_{i=1}^n\lambda_i\right). $$ A special case of this relation is very often used, namely when the $X_i$ are not only independently but also identically distributed. In that case, $S_n$ is $Po(n\lambda)$. As initially shown, this is quite easily shown using moment generating functions.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.